Determination of In Vitro and In Vivo Activities of Aloe Vera L. Against H. Pylori - CH. SANTHOSH KUMARI; CVN PRASAD; SREE RAMULU J (International Journal of Pharma and Bio Sciences, 2010)
Background: Antimicrobial and antiulcer activities of Aloe vera plant extract were evaluated against H. pylori strains. According to several studies, oral consumption of Aloe Vera works effectively to soothe conditions like heartburn, arthritis and rheumatism pain and asthma. Researchers are now investigating the new roles of antimicrobial and antiulcer activities of Aloe vera in acid peptic disorders. Therefore the current study is aimed to evaluate the anti-H. pylori and antiulcer properties of Aloe vera. Methods: The extracts of Aloe vera plants were harvested and stored for the in-vitro and in-vivo studies. The antimicrobial activity was detected by using disc diffusion method. In vivo activities were also studied in albino rats by ethanol induced ulcers and the treatment regimens. Results: The results showed that Aloe vera exhibited strong antimicrobial activity against H. pylori at two different concentrations of 250, 500µg/mL in comparison with standard Clarithromycin. In vivo studies showed a very good response in ulcer healing properties. Study found that use of Aloe vera may act as complementary and alternative medicine for gastrointestinal diseases.